A successful preterm vaccination program in a neonatal unit in a developing country. Issue 11 (November 2019) - Tooke, Lloyd; Louw, Byron
Abstract: Background: Although preterm infants are at a greater risk from vaccine preventable diseases, there are frequent delays in vaccine administration with great variability between units. There is little data from developing countries. Groote Schuur Hospital in Cape Town, South Africa starting vaccinating preterm infants from 2014. Objectives: To determine whether vaccines were given at the correct chronological age and whether there were side effects or logistical problems. Methods: For a six month period, all infants who were still admitted at 6 weeks of age were included. Date of vaccination and side effects were recorded. Results: 60 infants were included. 57 (95%) received their 6 week vaccines. 68% received the vaccines on time, 10% early and 17% late. Reasons for delay included oxygen dependence and concerns about sepsis. There were no side effects. Conclusions: It is possible to implement a successful vaccination program for preterm infants in a low resourced setting. Abstract : Public Health; Infectious Disease; Immune System; Vaccines; Pediatrics; Preterm; paediatrics; Vaccines